Model Pembinaan Kepala Sekolah Melalui Pendekatan Nilai Kearifan Lokal Kakaluargaan Untuk Meningkatkan Kompetensi Profesional Guru - Rahmi, Agustina; Redjeki, Dwi Sogi Sri; Eshariyani, Eshariyani; Rasuna, Rasuna; Pariyani, Riska Varna; Latifah, Antung (Jurnal Ilmiah Kanderang Tingang, 2024)
The aim of this research is to explore the model for coaching school principals through the application of local wisdom values ​​of Kakaluargaan to improve the professional competence of teachers at SMKN 3 Banjarbaru, implementation, and identify inhibiting factors and the solutions offered. This research uses qualitative methods with data collection techniques including observation, interviews and documentation. The results of the research show that the coaching model used by the Principal of SMKN 3 Banjarbaru is by: conducting assessments, analyzing, providing suggestions, evaluating and following up, involving senior teachers and motivating and providing guidance to teachers. Meanwhile, the implementation of the coaching model carried out by the school principal is by: a) carrying out supervision: carrying out pre-observation, observation, evaluation and follow-up; b) coaching outside supervision: sharing experience and knowledge in an effort to increase teacher professional competence. Meanwhile, the solution taken by the school principal if there are challenges and obstacles is to embrace, involve teachers in teacher professional development training, provide access to teacher professional development, teachers learn from colleagues and carry out evaluations and feedback.